Synthesis and characterization of mixed metal tungstate and titanates - Makhura, Ngwakwana Bridget (My University, 2011)
This dissertation investigates the synthesis of different mixed metal oxides using modern and classical synthetic techniques and their characterization by powder x-ray diffraction (PXRD) techniques and structure refinement using Rietveld. The ex situ and in situ variable temperature PXRD studies were performed to determine the structure of all the materials, thermal behaviour and quantitative Rietveld phase analysis of the synthesized oxides. Lead tungstate, niobium tungstate mixture, nickel titanate and nickel tungstate are the materials used in the study. The main characteristic studied was the thermal behaviour using the in situ thermal studies to determine the co efficient of thermal expansion.